2000
DOI: 10.1097/00000539-200002000-00035
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics and Analgesic Efficacy of Larger Dose Rectal Acetaminophen (40 mg/kg) in Adults: A Double-Blinded, Randomized Study

Abstract: Acetaminophen pharmacokinetics were comparable in adults and children. Plasma concentrations known to reduce fever did not produce better pain relief and were only achieved after twice the conventional dose was administered. Analgesic plasma concentrations have yet to be determined but may be higher than those associated with antipyresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…The analgesic efficacy of paracetamol is equivalent to that of aspirin, while its plasma levels required for the analgesic activity are higher than those needed for the antipyretic activity (18).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…The analgesic efficacy of paracetamol is equivalent to that of aspirin, while its plasma levels required for the analgesic activity are higher than those needed for the antipyretic activity (18).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…dose of only 5 mg/kg paracetamol (administered as propacetamol), by which an initial serum concentration of 14 mg/L was reached, yielded sufficient analgesia [9]. A study by Beck et al demonstrated a C max of only 10.4 mg/L and 17.2 mg/L after rectal administration of paracetamol at 20 mg/kg and 40 mg/kg, respectively [10]. Furthermore, another study compared the bioavailability of paracetamol after oral and i.v.…”
Section: Introductionmentioning
confidence: 99%
“…Beck et al carried out a study among patients undergoing gynecological surgery involving vaginal and abdominal hysterectomies, in which they used paracetamol 20 mg/kg, 40 mg/kg alone and paracetamol 20 mg/kg single rectal dose in combination with diclofenac sodium 100 mg with a observational period of 24 hour after surgery, the result showed that combination of drugs had better pain management than paracetamol alone [8]. Breivik et al carried out study in patients undergoing dental surgery with impacted ΙΙΙrd molar tooth, he used diclofenac 100 mg, paracetamol 1000 mg alone and diclofenac 100 mg with paracetamol 1000 mg single rectal dose with 8 hours of observational period [9].…”
Section: Discussionmentioning
confidence: 99%